IMPLICATIONS OF THE NEW 2019 HAGUE CONVENTION ON RECOGNITION AND ENFORCEMENT OF FOREIGN JUDGMENTS ON THE NATIONAL LEGAL SYSTEMS OF COUNTRIES IN SOUTH EASTERN EUROPE (EU and comparative law issues and challenges series (ECLIC), 2019)
The diplomatic session of the Hague Conference on Private International Law (Hague Conference) regarding the “Judgments Project” will be held between 18 June – 02 July 2019 in the Hague when it is expected that the long awaited Hague Convention on Recognition and Enforcement of Foreign Judgments (new 2019 Hague Convention) will be adopted. This Convention comes as a result of 27 years of work that has been done in the course of this project of the Hague Conference and it can be said that is one of the most awaited developments in Private International Law. The success of the convention cannot be predicted at this point because large number of factors impact the outcome of the convention. However benefits from having an international agreement dealing with cross border recognition and enforcement of foreign judgments is self-evident. More than ever there is a need of a single instrument that will contain unified conditions for recognition and enforcement and ease the cross border circulation of judgments. Only a brief look at the New York Convention on recognition and enforcement of foreign arbitral awards (New York Convention) provides for glimpse of the benefits from having such instrument. So what will this mean for the countries of South Eastern Europe? What will be the interest of the countries to be part of this Convention? How much are the national legal systems compatible with the rules provided in the Hague convention? This article will try to answer these questions, together with the implications that the Hague Convention will have on the South Eastern Europe region. Moreover this is of huge importance since most of the countries of South Eastern Europe region are part of the European Union or are candidate countries. So has the time come for a structural change of the national recognition and enforcement systems and how far reaching will be the consequences on the national legal systems?